A long walk to water - Park, Linda Sue (Boston : Houghton Mifflin Harcourt, 2015)
When the Sudanese civil war reaches his village in 1985, eleven-year-old Salva becomes separated from his family and must walk with other Dinka tribe members through southern Sudan, Ethiopia, and Kenya in search of safe haven. Based on the life of Salva Dut, who, after emigrating to America in 1996, began a project to dig water wells in Sudan.
"Based on a true story."
Includes "A message from Salva Dut, Rochester, New York, 2010", and "Author's note" with "Addendum, 2015."
Grades 6 & up.
720L
Accelerated Reader AR.
Accelerated Reader AR
Keywords: Dut, Salva, -- 1974- -- Juvenile fiction; Dut, Salva, -- 1974- -- Fiction; Dut, Salva, -- 1974- -- Fiction; Water for South Sudan, Inc; Refugees -- Juvenile fiction; Survival -- Juvenile fiction; Water-supply -- Juvenile fiction; Blacks -- Sudan -- Juvenile fiction; Children and war -- Juvenile fiction; War stories -- Juvenile fiction; Orphans -- Juvenile fiction; Lost Boys of Sudan -- Juvenile fiction; Sudan -- History -- Civil War, 1983-2005 -- Juvenile fiction; Sudan -- Juvenile fiction; South Sudan -- Juvenile fiction; Authors' autographs (Provenance) -- Park -- 2010.; War fiction; Biographical fiction